Performance Analysis of Empennage Configurations on a Surveillance and Monitoring Mission of a VTOL-Plane UAV Using a Computational Fluid Dynamics Simulation - Nugroho, Gesang; Zuliardiansyah, Galih; Rasyiddin, Azhar Aulia (MDPI, 2022)
A Vertical Take-Off and Landing-Plane (VTOL-Plane) is an Unmanned Aerial Vehicle (UAV) that combines multirotor and fixed-wing configurations. It has a good cruise range compared to a VTOL vehicle. Furthermore, it can take-off and land vertically. This technology is ideal for surveillance/monitoring missions and transmitting data in real-time. This study discusses the design of a VTOL-Plane with a preset Design Requirement Objectives (DRO), namely a Maximum Take-Off Weight (MTOW) of 14 kg, a cruise speed of 23 m/s, and a cruising range of 6 h. To maximize the performance, the empennage configurations on the VTOL-Plane varied, and then a Computational Fluid Dynamics (CFD) simulation was carried out. The empennage configurations analyzed were a U-shaped boom, an inverted U-shaped boom, an inverted V-tail boom, and a semi-inverted V-tail boom. The interpreted performance related to the stalling angle, flight efficiency, stability, stall speed, and maneuverability. The relative wind directions toward the longitudinal axis of the UAV, also called the sideslip angle, were varied. The CFD simulation results showed that the empennage configuration of the inverted U-shaped boom is suitable for a surveillance mission. This article also optimized the final empennage design by adding a vertical fin to improve stability. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.